Guido Piccoli, Giuseppe Palumbo, Escobar. El Patrón. (Milano, Mondadori, 134 pp., ISBN 97884681656) (Altre Modernità, 2017)
Guido Piccoli, Giuseppe Palumbo, Escobar. El Patrón. (Milano, Mondadori, 134 pp., ISBN 97884681656)di Simone Ferrari